Matkailunkestävä Suomi? Vastuullinen suunnittelu kulttuuri- ja luontoympäristöissä - Veijola, Soile (Tietolipas, 2023)
Tourism must be planned and developed differently from what is customary today, as growth in rigid economic terms is still prioritised over the cultural and socioecological sustainability of lived-in cultural and natural environments. The global ecological crisis can no longer be ignored by tourism developers and investors - or by tourists. The seventeen authors of this book are from a variety of disciplines and fields of expertise. Through research-driven and profession based knowledge on different aspects of tourism planning in Finland and elsewhere, they offer transformative perspectives and practical applications for responsible tourism planners, investors and political decision-makers to utilise. Through the book's overarching themes - learnings from the history of tourism planning, wellbeing, participation, building and architecture, people and infrastructure - it addresses a general audience, professional communities, and academic communities. The book's urgent quest is to prevent tourism from remaining one of the causes for the greatest problem of all time, the worsening baseline of living conditions on Earth.